Pengaruh Pengajaran Pendidikan Agama Kristen dan Spiritualitas Guru Agama Kristen Berdasarkan Titus 2:6-8 Terhadap Pertumbuhan Karakter Kristiani Siswa SMAN 1 Wamena - Mikhayani Barasa, Chrisna; Minggus (Student Evangelical Journal Aiming At Theological Interpretation, 2024)
This study is based on observations of high school students in Wamena who tend to mimic behaviors, including those of religious teachers, which may not be appropriate for their age. Researchers suspect this is related to a lack of seriousness in learning. The study aims to prove the relationship between teaching Christian Religious Education based on Titus 2:6-8 and the spirituality of Christian religious teachers with the growth of students' Christian character. This research is quantitative with a descriptive analysis approach. The sample consists of 64 respondents selected using Simple Random Sampling. The results show that the influence of teaching Christian Religious Education based on Titus 2:6-8 on the growth of students' Christian character is high (79.2%), as well as the spirituality of Christian religious teachers (97.5%). Both together have a high influence (94.1%).